Pengaruh Budaya Organisasi Dan Komitmen Organisasi Terhadap Kinerja Karyawan Dengan Motivasi Kerja Sebagai Variabel Intervening Di Qur'an Centre Provinsi Kepulauan Riau - Adi Syahputra Purba; M Ilham Fathoni (CERED Indonesia Institute, 2021)
The effect of the X1 variable on X3 has a P-Values value of 0.000 <0.05, so it can be stated that the effect of X1 on X3 is significant. The effect of the X1 variable on Y has a P-Values value of 0.016 <0.05, so it can be stated that it has a significant effect. The effect of the X2 variable on X3 has a P-Values value of 0.000 <0.05, so it can be stated that it has a significant effect. The effect of the X2 variable on Y has a P-Values value of 0.030 <0.05, so it can be stated that it has a significant effect. The effect of the X3 variable on Y has a P-Values value of 0.013 <0.05, so it can be stated that it has a significant effect. The indirect effect of the X1 variable on Y through X3 has a P-Values value of 0.032 <0.05, so this result shows that X1 indirectly has a significant effect on Y through X3. The indirect effect of the X2 variable on Y through X3 has a P-Values value of 0.028 <0.05, so this result shows that X2 indirectly has a significant effect on Y through X3.